2016
DOI: 10.1002/cm.21304
|View full text |Cite
|
Sign up to set email alerts
|

Tropomodulin isoforms utilize specific binding functions to modulate dendrite development

Abstract: Tropomodulins (Tmods) cap F-actin pointed ends and have altered expression in the brain in neurological diseases. The function of Tmods in neurons has been poorly studied and their role in neurological diseases is entirely unknown. In this paper we show that Tmod1 and Tmod2, but not Tmod3, are positive regulators of dendritic complexity and dendritic spine morphology. Tmod1 increases dendritic branching distal from the cell body and the number of filopodia/thin spines. Tmod2 increases dendritic branching proxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(48 citation statements)
references
References 78 publications
3
37
0
Order By: Relevance
“…This pathway regulated motility and altered cell shape, which are known to be altered by changes in Tmod expression (Fath et al, 2011; Fischer et al, 2003; Guillaud et al, 2014; Moroz et al, 2013a). We have shown that overexpression of Tmod1 increases the complexity of the dendritic arbor (Gray et al, 2016). These two observations suggest that upregulation of Tmod1 via wnt signaling could be a mechanism by which the brain may signal to increase dendritic complexity.…”
Section: Tropomodulins and Tropomyosins – Discovery Structure And Rmentioning
confidence: 97%
See 3 more Smart Citations
“…This pathway regulated motility and altered cell shape, which are known to be altered by changes in Tmod expression (Fath et al, 2011; Fischer et al, 2003; Guillaud et al, 2014; Moroz et al, 2013a). We have shown that overexpression of Tmod1 increases the complexity of the dendritic arbor (Gray et al, 2016). These two observations suggest that upregulation of Tmod1 via wnt signaling could be a mechanism by which the brain may signal to increase dendritic complexity.…”
Section: Tropomodulins and Tropomyosins – Discovery Structure And Rmentioning
confidence: 97%
“…While Tpms and Tmods are intimately related at the pointed ends of actin filaments, only one paper has studied the importance of their interaction in neurons (Gray et al, 2016). Here we will explore the known roles of Tpms and Tmods on the formation of growth cones, dendrites, dendritic spines, and axons.…”
Section: Tropomodulins and Tropomyosins Regulate Neuronal Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…48 A recent study demonstrated that TMOD2 is a positive regulator of dendritic complexity and spine morphology. 49 Cannabis use is well known to have a significant impact on brain structures that are enriched with cannabinoid receptors. 50 Although no other studies have verified this hypothesis yet (to date we can identify only 13 articles regarding TMOD2 function), we speculate that TMOD2 could be involved in the remodelling processes induced by cannabis use in brain areas relevant to sexual function and behaviours.…”
Section: Discussionmentioning
confidence: 99%